Perbedaan Hasil Belajar Mahasiswa PGSD UNIPA Surabaya dengan Model Mnemonik pada Materi Peta, Atlas dan Globe Ditinjau dari Gaya Belajar Audio, Visual dan Kinestetik - Danang Prastyo; Anturi Anturi; Arif Mahya Fanny (Universitas Sarjanawiyata Tamansiswa, 2017)
Abstract: This research aimed to know the differences of the studentsâ€™ learning style of PGSD students of UNIPA Surabaya by using mnemonic model on map material, atlas and globe which is viewed from audio, visual, kinesthetic learning style. The population of this study is the students of PGSD UNIPA Surabaya and the sample of this research is the students of C class 2016. This research is using the survey research. The design of this research is using the statistic parametric one way anova. The data analysis is using the analysis of inferential statistics by using the SPSS version 18. From the analysis of research data shows the significance of students learning results of PGSD class C 2016 is 0,195 greater than 0,05. It means that there is no differences of the result of the students; learning style of PGSD UNIPA Surabaya with the mnemonic model inthe material of map, atlas and globe which is viewed from the audio, visual and kinesthetic learning style. While for the learning resultÂ of PGSD UNIPA Surabaya students with mnemonic model, it is seen that the students with auditory learning style were the highest with average score of 73,42, followed by kinesthetic learningÂ with average score equal to 71.00 and visual learning style with average value of 69.33 and style.